Landscape pattern has greater influence than local vegetation on songbirds along rights-of-way in forest-dominated landscapes - Eric L. Margenau; Petra B. Wood; Christopher W. Ryan (PLoS ONE, 2026)
The proliferation of linear energy infrastructure (e.g., pipelines, powerlines) in forested landscapes throughout North America has advanced the need to understand how to manage these areas for improved species conservation. Habitat management implemented to use the unique vegetative characteristics associated with energy corridors may be a promising direction for future conservation. For songbirds, responses to habitat change can vary based on vegetative characteristics at local and landscape scales. Therefore, a better understanding of how vegetative characteristics across spatial scales affect songbird responses to habitat management that is associated with linear energy infrastructure is necessary for developing proactive solutions. We assessed songbird abundance and richness at point count locations within silviculture treatments along energy corridors (pipelines and powerlines) to habitat characteristics at local (within 100 meters surrounding point counts) and landscape (within 500 meters) scales in West Virginia, USA during 2017–2019. Landscape variables had greater influence on songbirds in silviculture treatments compared to local variables. Species- and community-level responses to variables varied depending on habitat guild association, with some within-guild species responding to the same variable in opposing directions. The proportion of young forest habitat and the size of the nearest young forest patch surrounding silviculture treatments had the strongest influences on songbirds of all landscape variables considered. The width of the right-of-way adjacent to silviculture treatments had the strongest influence on songbirds of all local variables considered. These results suggest that consideration of the surrounding landscape is important when planning habitat management in forested areas in association with linear energy infrastructure.